Asymmetric sulfonated polysulfone cation exchange membranes prepared by non-solvent induced phase separation for reverse electrodialysis using desalination brines - Aquino, Marco; Santoro, Sergio; Avci, Ahmet Halil; Tufa, Ramato Ashu; Bouzek, Karel; Straface, Salvatore; La Russa, Mauro Francesco; Davoli, Mariano; Politano, Antonio; Politano, Grazia Giuseppina; Aceti, Dante Maria; Palermo, Giovanna; et al. (Electrochimica Acta, 2025)
The transition to sustainable energy is crucial for modern society, and Reverse Electrodialysis (RED) offers a promising method for harvesting energy from salinity gradients. However, large-scale deployment of RED is constrained by efficiency limitations and the high cost of ion exchange membranes. This study focuses on the development of novel asymmetric cation exchange membranes (CEMs) based on sulfonated polysulfone (SPSf) prepared via non-solvent induced phase inversion (NIPS). The highest degree of sulfonation achieved was 0.50, which optimized the balance between electrochemical membrane properties and the processability for CEMs preparation. CEMs properties were further fine-tuned by adjusting the polymer solution composition, with optimal performance achieved using a 20 wt% of 2-propanol as co-solvent in dimethylformamide. Electrochemical characterization under various saline conditions demonstrated favourable transport properties of the optimized CEMs. When tested in RED, the membrane achieved a maximum power density of 220 mW·m⁻² per cell pair under a 0.1 M/0.5 M NaCl gradient, comparable to commercial CEMs under similar conditions. These results highlight the potential of the developed membranes to advance RED technology, providing an economically viable and efficient solution for salinity gradient energy conversion.
Keywords: Brine; Cation exchange membranes; Reverse electrodialysis; Salinity gradient energy; Sulfonated polysulfone